CD28 Aptamers as Powerful Immune Response Modulators - Fernando Pastor; Mario M Soldevilla; Helena Villanueva; Despina Kolonias; Susana Inoges; Ascensión L de Cerio; Romy Kandzia; Victor Klimyuk; Yuri Gleba; Eli Gilboa; Maurizio Bendandi (Elsevier, 2013)
CD28 is one of the main costimulatory receptors responsible for the proper activation of T lymphocytes. We have isolated two aptamers that bind to the CD28 receptor. As a monomer, one of them interfered with the binding of CD28 to its ligand (B7), precluding the costimulatory signal, whereas the other one was inactive. However, dimerization of any of the anti-CD28 aptamers was sufficient to provide an artificial costimulatory signal. No antibody has featured a dual function (i.e., the ability to work as agonist and antagonist) to date. Two different agonistic structures were engineered for each anti-CD28 aptamer. One showed remarkably improved costimulatory properties, surpassing the agonistic effect of an anti-CD28 antibody. Moreover, we showed in vivo that the CD28 agonistic aptamer is capable of enhancing the cellular immune response against a lymphoma idiotype and of prolonging survival of mice which receive the aptamer together with an idiotype vaccine. The CD28 aptamers described in this work could be used to modulate the immune response either blocking the interaction with B7 or enhancing vaccine-induced immune responses in cancer immunotherapy.